Simplify, if x = 2 and y = -1: 3(y + 2)^2 + 3x

Asked 11 months ago
Viewed 729117 times
1
Simplify, if x = 2 and y = -1: 3(y + 2)^2 + 3x

1 Answer

2

Answer:

9

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Step-by-step explanation:

Step 1: Define

3(y + 2)² + 3x

x = 2

y = -1

Step 2: Evaluate

  1. Substitute:                    3(-1 + 2)² + 3(2)
  2. Add:                              3(1)² + 3(2)
  3. Exponents:                   3(1) + 3(2)
  4. Multiply:                        3 + 6
  5. Add:                              9
Edit
avatar
Jayde Schoen
15.5k 3 10 26
answered 11 months ago